The role of muscle proteases and lipases in flavor development during the processing of dry-cured ham - Toldra, F. (C.S.I.C., Valencia, Spain.); Flores, M (Critical reviews in food science and nutrition, 1998)
The processing of dry-cured ham is very complex and involves numerous biochemical reactions that are reviewed in this article. Muscle proteins undergo an intense proteolysis, resulting in a great number of small peptides and high amounts of free amino acids. The enzymes responsible of these changes are proteinases (cathepsins B, D, H, and L and, to a less extent, calpains) and exopeptidases (peptidases and aminopeptidases). Muscle and adipose tissue lipids are also subject to intense lipolysis, generating free fatty acids by the action of lipases that, in a second stage, are transformed to volatiles as a result of oxidation. Sensory profiles of dry-cured ham are strongly affected by these enzymatic reactions. In addition, the activity levels of the muscle enzymes significantly depend on the properties of raw ham, such as age and crossbreeding as well as the process conditions such as temperature, time, water activity, redox potential, and salt content. Thus, the control of the muscle enzyme systems, mainly proteases and lipases, is essential for the standardization of the processing and/or enhancement of flavor quality of dry-cured ham